Malaria in Complex Emergencies: A Review. - Obongama O. Edet* and Emmanuel A. Omon (Sokoto Journal of Medical Laboratory Science)
Malaria is a life threatening and communicable disease of the tropical and subtropical areas with attendant morbidity and mortality. It is associated with conflict and flourishes in conditions of crisis and population displacement such as in complex emergencies. In complex emergencies, malaria is a significant cause of death and illness. Population movement of non- immune people to endemic areas, lack of access to health care and gaps in medication supply chain and loss of human capital are factors of complex emergencies and contribute to the malaria burden. Vector control and personal protection using indoor residual spray and insecticide treated nets are effective prevention strategies aside using appropriate therapies for malaria management. Effective strategies focusing on communities in complex emergencies to reduce malaria burden can be by way of education, proper information and communication. In any case, complex emergencies deserve special attention to reduce malaria burden. This review provides understanding into complex emergencies and applicable information to reduce malaria burden.